2016
DOI: 10.1589/jpts.28.788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a walking exercise program for obese individuals with intellectual disability staying in a residential care facility

Abstract: The purpose of this study was to confirm the critical importance of active obesity management through a fitness program, and to provide foundational data required for effective obesity management of disabled persons residing in residential carse facilities. [Subjects and Methods] The study period lasted 16 weeks, from August 1 to November 30, 2014. The study participants comprised 9 individuals and they participated in a walking exercise program. An occupational therapist assessed each participant’s body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
(9 reference statements)
0
14
0
4
Order By: Relevance
“…Findings suggest obesity management and prevention efforts require multifaceted strategies incorporating education, health policy, public health and health systems, strong primary care workforce, etc 16 ) . The findings suggest that, among Korean, walking exercise programs should be offered to obese and implemented as a continuous program 17 ) . Research found that aerobic exercise reduces weight and improves cardiopulmonary fitness in obese subjects more effectively than anaerobic exercise 18 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggest obesity management and prevention efforts require multifaceted strategies incorporating education, health policy, public health and health systems, strong primary care workforce, etc 16 ) . The findings suggest that, among Korean, walking exercise programs should be offered to obese and implemented as a continuous program 17 ) . Research found that aerobic exercise reduces weight and improves cardiopulmonary fitness in obese subjects more effectively than anaerobic exercise 18 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mechanisms of the exercise effectiveness such as prevention of chronic inflammation and oxidative stress cannot be overlooked. Nevertheless, few PA interventions have resulted in weight loss in youths [ 60 ] or adults with ID [ 61 ], suggesting no salient relationship between PA and BMI in this population. Thus, more studies on the impact of PA on the body composition of adults with ID are required [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increase the physical movement through abdominal muscle exercise has an influence to raise energy consumption and burn the body fat cells. As a result, the weight showed the decrease as much as consumed body fat cells11 ) .…”
Section: Discussionmentioning
confidence: 99%
“…to 5.6 cm. It has been shown that contraction and relaxation from abdominal muscle exercise improve flexibility 11 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation